COVID-19 as a Window for Equity-Oriented School Leadership: What Have we learned From Principals’ COVID-19 Response? (Journal of School Administration Research and Development, 2024)
This essay argues that principals' capacity to advance equity might have been constrained by pre-COVID conditions. Drawing on the emerging literature on school leadership during the pandemic, the current article discusses how principals' capacity to advance equity was expanded as a result of the window of opportunities created by the COVID-19 pandemic. Given the increased frequency at which schools experience crises, understanding these opportunities may allow stakeholders to better support principals' efforts to enact equity-oriented leadership practices. Implications for leadership preparation, school funding, accountability policies, and future research are discussed.